2005
DOI: 10.1111/j.1365-2664.2005.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slash harvest on bryophytes and vascular plants in southern boreal forest clear‐cuts

Abstract: Summary1. Slash harvesting from forests to provide bioenergy reduces the amount of woody debris in the managed forest landscape and changes the physical and chemical environment in clear-cuts. We examined previously unstudied effects of commercial (i.e. nonexperimental) slash harvest on species composition and richness of liverworts, mosses and vascular plants. The results call for modification of commercial slash harvest practices. 2. Differences between conventionally harvested (i.e. slash left) and slash-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 37 publications
1
25
2
1
Order By: Relevance
“…Mosses and liverworts may respond differently because most moss species are less shade adapted and drought sensitive than the majority of liverworts (Marschall and Proctor 2004). Hence, moss richness is less affected by exposure (Fenton et al 2003, Å stro¨m et al 2005, Hylander et al 2005. Furthermore, forest species, and species associated with convex substrates such as logs, stumps, and tree bases, are more prone to local extinction following clear-cutting .…”
Section: Introductionmentioning
confidence: 99%
“…Mosses and liverworts may respond differently because most moss species are less shade adapted and drought sensitive than the majority of liverworts (Marschall and Proctor 2004). Hence, moss richness is less affected by exposure (Fenton et al 2003, Å stro¨m et al 2005, Hylander et al 2005. Furthermore, forest species, and species associated with convex substrates such as logs, stumps, and tree bases, are more prone to local extinction following clear-cutting .…”
Section: Introductionmentioning
confidence: 99%
“…If such necessary near future protected area expansions are not accounted for when considering restrictions to the allocation of bioenergy areas, the scenarios remain unrealistic, adding further challenges to the conservation of biodiversity. Moreover, further increases in the coverage of protected areas will be necessary to meet biodiversity targets, especially as the ranges of species are predicted to shift as a response to climate change (Araújo et al 2011;Hannah et al 2007;Hannah et al 2002;Heller and Zavaleta 2009). More generally, several studies recommend mainstreaming biodiversity conservation throughout land-use planning so that the landscape managed for economic purposes would remain biodiversity friendly (Hannah et al 2002;Noss 2001;Wilson and Piper, 2008).…”
Section: Key Limitations Of Global Land-use Scenarios From the Perspementioning
confidence: 99%
“…Reported effects of increased biomass removal on boreal forest vegetation differ (e.g. Åström et al, 2005;Olsson & Staaf, 1995). Fahey et al (1991) found that grass biomass increased more rapidly after WTH compared with SOH and continued to make up a higher proportion of the biomass during the first four years after harvesting, while Bergquist et al (1999) found no effects of WTH on grasses.…”
Section: Effects Of Harvesting Intensity On Biological Diversitymentioning
confidence: 99%